KEBIASAAN MAKAN, ASUPAN ENERGI DAN ZAT GIZI, AKTIVITAS FISIK, DAN KADAR GLUKOSA DARAH REMAJA OVERWEIGHT DI KOTA BLITAR JAWA TIMUR - Sutjiati, Endang; Saputri, Destri Amalia (Program Studi Ilmu Gizi, Jurusan Kesmas Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2022)
This study was to examine eating habits, energy and nutrient intake, physical activity and blood glucose levels of overweight adolescents in Blitar city. Descriptive qualitative research method with case study design. The research subjects were 30 high school students in the overweight nutritional status category. Eating habits, energy intake and nutrients were measured using the FFQ method and 2 x 24 hour recall, physical activity using the PAL method and blood glucose levels using a glucometer. A total of 30 overweight adolescents, 25 female and 7 male, had a BMI between 25-29. Overweight adolescents have unbalanced eating habits and do not usually eat breakfast or dinner, the type of food consumed has a low glycemic index with a portion less than the RDA. Energy and nutrient intakes include a severe deficit (<70% of the RDA), physical activity including light and blood glucose levels when the lowest is 81 mg/dl and the highest is 144 mg/dl. It was concluded that overweight adolescents consumed unbalanced food, did not get adequate energy and nutrient intake, and had low activity. Blood glucose levels tend to be high and can be a major risk factor for type 2 diabetes.